Algorithms of Air Law - Connecting the Dots - Abeyratne, Ruwantissa (Frontiers in Law, 2025)
Rapid developments in the aviation industry bring to bear the compelling need to reexamine algorithms in air law. For example, the advent of advanced air mobility (AAM), typified by eVTOL aircraft and algorithm-driven systems, compels an evaluation of traditional air law. Rooted in treaties such as the Paris Convention of 1919 and the Chicago Convention of 1944, air law has evolved incrementally in response to the growth of global aviation. However, the rapid emergence of technologies such as autonomous aircraft, drones, and quantum computing necessitates a transformative approach. Algorithms, once peripheral to legal considerations, now lie at the heart of this evolution. These systems provide not only a means of optimizing safety and efficiency but also an avenue for addressing the intricate interplay of liability, governance, and ethical considerations. The Council of the International Civil Aviation Organization (ICAO) stands at the forefront of this transformation. Leveraging its role as a global standard-setter, the Council can convene stakeholders to develop adaptive legal instruments, emphasizing cybersecurity protocols, liability apportionment, and equitable access. By fostering interdisciplinary collaboration and engaging in proactive governance, ICAO can ensure that AAM integrates innovation with fairness and resilience. Ultimately, the integration of algorithms into air law represents more than a technological shift; it demands a philosophical reorientation. The algorithm emerges not only as a tool but also as a metaphor for interconnectedness and adaptability. Air law, in embracing this paradigm, must transcend prescriptive rules to become a living, dynamic framework capable of guiding aviation into an equitable, sustainable future. Only through such an approach can we ensure that the skies remain navigable, secure, and just, reflecting a balance between technological progress and human values. This article examines the issues involved.